Employment subsidies and substitutable skills: an equilibrium matching approach - Gabriele Cardullo; Bruno van der Linden (Institute for the Study of Labor (IZA), 2006)
The search-matching model is well suited for an equilibrium evaluation of labor market policies. When those policies are targeted on some groups, the usual juxtaposition of labor markets is however a shortcoming. There is a need for a setting where workers' productivity depends on employment levels in all markets. This paper provides such a theoretical setting. We first develop a streamlined model and then show that it can be extended to deal with interactions among various labor market and fiscal policies. Simulation results focus on the effects of employment subsidies and in-work benefits and on their interactions with the profile of unemployment benefits and with active labor market programs.
Keywords: E24; J3; J41; J64; J65; J68; 330; unemployment; search-matching equilibrium; wage bargaining; reductions of social security contributions; unemployment insurance; labor market programs; Arbeitsmarktpolitik; Lohnsubvention; Ungelernte Arbeitskräfte; Beschäftigungseffekt; Sozialversicherungsbeitrag; Arbeitslosenversicherung; Arbeitsplatzsuchmodell; Simulation